THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT PRACTICES AND JOB INVOLVEMENT ON THE EMPLOYEE PERFORMANCE IN THE PUBLIC SERVICE SECTORS MEDIATED BY AFFECTIVE COMMITMENT - Verlina Dwi Pamungkas; Fitri Wulandari (IAIN Surakarta, 2021)
This study aims to analyze the influence of Human Resource Management (HRM) practices and job involvement on the employee performance of the public service sectors mediated by affective commitment. The sample in this study was 105 employees who work in the public sector. This study used path analysis employing the IBM SPSS 22 software. The results of this study indicate that there is a positive and significant influence of HRM practices in the public service sectors on employee performance and there is a positive and significant influence of job involvement on employee performance as well as the positive and significant influence of affective commitment to employee performance. The results also show that affective commitment does not mediate either partially or fully the influence of HRM practices on the performance of employees in the public service sectors. In addition, affective commitment also does not mediate either partially or fully the effect of job involvement on the performance of employees in the public service sectors. The best strategy proposed in this study is how to encourage the role of job involvement in the form of increased participation, work flexibility, empowerment, and wider responsibility to increase affective commitment and employee performance.